Educational guidance from the teacher's perspective in complex times (Revista Electrónica REDINE, 2026)
Guidance is, above all, an act of human accompaniment; it is not an isolated process. On the contrary, it is a psychosocial action that emerges at the heart of educational institutions. As Casado (2005) explains, its scope transcends the individual to encompass their environment: family, peers, and the educational community in general. From this perspective, educational guidance and education complement each other to offer affective, spiritual, social, and emotional well-being within educational institutions as part of the teaching and learning process. However, everyday situations such as immigration, social media, and bullying have impacted students and altered the school climate, prompting immediate intervention to address the situations that arise within the classroom dynamic and affect students' learning process. However, everyday situations such as immigration, social media, and bullying have impacted students, altering the school climate and necessitating immediate intervention to address the issues arising in the classroom and affecting students' learning. The counselor's role has been limited to simply providing support; ideally, it should focus on preventative and developmental intervention to continuously address these situations within educational institutions. The inclusion of parents and guardians is imperative, and they should be provided with support through family education programs so they can assist teachers in their guidance, academic, and personal development. In this new millennium, guidance requires a response to its function, closely linked to the application of educational resources for a learning and research environment that establishes its social relevance in light of current social demands and scientific developments in the field. It is necessary to contribute to the development of other theories that enrich guidance within its educational practice, in order to address the emerging needs of students in the classroom, education, inclusion, the workplace, and teacher quality.
Keywords: complexity; teacher; educational guidance; educational practice